Chronic Pain Treatment: The Influence of Tricyclic Antidepressants on Serotonin Release and Uptake in Mast Cells - Ilonka Ferjan; Metoda Lipnik-Štangelj (Hindawi Limited, 2013)
The involvement of serotonin (5-HT) in chronic pain mechanisms is established. 5-HT inhibits central painful stimuli, but recent data suggests that 5-HT could also enhance pain stimulus from the periphery, where mast cells play an important role. We aimed in our study to clarify the influence of selected tricyclic antidepressants (TCAs) on mast cell function: secretion, uptake, and reuptake of 5-HT, that could interfere with 5-HT levels and in this way contribute to the generation of pain. As an experimental model, we used isolated rat peritoneal mast cells and incubated them with selected TCAs (clomipramine, amitriptyline, doxepin, and imipramine) under different experimental conditions. 5-HT release, uptake, and reuptake were determined spectrofluorometrically. We showed that TCAs were able to inhibit 5-HT secretion from mast cells, as well as uptake of exogenous 5-HT and reuptake of secreted 5-HT back into mast cells. The effects of TCAs were concentration dependent; higher concentrations of TCAs inhibited the secretion of 5-HT induced by compound 48/80, whereas lower concentrations of TCAs inhibited 5-HT uptake. The most effective TCA was halogenated clomipramine. As TCAs are well introduced in chronic pain treatment, the insight into mechanisms of action is important for an understanding of their effect in various pain conditions.